Unexpected Equilibrium Ionic Distribution in Cyanine/C60 Heterojunctions. Issue 5 (19th December 2016) - Jenatsch, Sandra; Groenewold, Jan; Döbeli, Max; Hany, Roland; Crockett, Rowena; Lübben, Jörn; Nüesch, Frank; Heier, Jakob
Abstract : The equilibrium ionic distribution in cyanine donor–fullerene acceptor bilayer systems is investigated using Rutherford backscattering spectroscopy, elastic recoil detection analysis, and time‐of‐flight secondary ion mass spectroscopy. Simultaneously, the potential profile inside the C60 layer is followed by Kelvin probe force microscopy. Experimental verifications are obtained by using different device architectures, different mobile counter ions, and alternative acceptor layers. The unexpected constant iodide profile inside C60 and the potential shift close to the donor–acceptor interface can be explained by an exchange of electrons and ions from acceptor to donor and vice versa. The proposed model explaining all of the observed experimental findings is supported by a thermodynamic model. Abstract : The equilibrium ion distribution and electronic potential shift at the heterojunction of a cationic cyanine dye and the electron acceptor C60 are investigated. Massive ion diffusion into C60 is observed that is in contradiction to current models. A picture that includes doping of C60 by the counter ions accounts for all observations.